2011
DOI: 10.1258/phleb.2010.009092
|View full text |Cite
|
Sign up to set email alerts
|

Compression versus sclerotherapy for patients with isolated refluxing reticular veins and telangiectasia: a randomized trial comparing quality-of-life outcomes

Abstract: Isolated refluxing reticular and telangiectatic vein disease may cause QoL impairment in select patients and represent far more than a cosmetic concern. Compression therapy offers relief of aching, pain, leg cramping and restlessness in patients with isolated refluxing reticular veins and telangiectasia. Sclerotherapy of reticular veins offers a statistically superior broad spectrum relief of symptoms, while additional sclerotherapy of residual telangiectasia in this cohort demonstrated additive relief of achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
1
12
0
2
Order By: Relevance
“…A prospective randomised study that compared thigh-high compression stockings (20–30 mmHg) with sclerotherapy in patients with C1 CVD showed that compression therapy provides significant relief of aching (p < 0.0001), pain (p = 0.002), leg cramps (p = 0.003) and restlessness (p < 0.05), while sclerotherapy provides superior broad-spectrum symptom relief. 11 Furthermore, in two prospective randomised studies in patients with mild, moderate or severe CVD, Couzan et al. 12 , 13 compared progressive compression stockings (i.e.…”
Section: Recommendationsmentioning
confidence: 99%
“…A prospective randomised study that compared thigh-high compression stockings (20–30 mmHg) with sclerotherapy in patients with C1 CVD showed that compression therapy provides significant relief of aching (p < 0.0001), pain (p = 0.002), leg cramps (p = 0.003) and restlessness (p < 0.05), while sclerotherapy provides superior broad-spectrum symptom relief. 11 Furthermore, in two prospective randomised studies in patients with mild, moderate or severe CVD, Couzan et al. 12 , 13 compared progressive compression stockings (i.e.…”
Section: Recommendationsmentioning
confidence: 99%
“…Venous symptoms adversely affecting QoL parameters may be more common than previously suspected and severity may not correlate to the size or type of refluxing veins. 44 The ideal treatment for varicose veins should be relatively noninvasive, repeatable if necessary, relatively safe, and free of significant complications. The fact that there has been no previous meta-analysis comparing surgery with other techniques for the treatment of varicose veins strictly in terms of QoL suggests that changes in QoL and symptomatic follow-up of these patients are much more difficult to measure than simple technical recurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support the use of ECS is also extrapolated from the CVI literature. Randomized trials comparing ECS to no intervention [106,107], low to high pressure ECS [108,109] and ECS to sclerotherapy [110] have demonstrated relief of symptoms with ECS. Guidelines also recommend ECS for CVI [111].…”
Section: Should Compression Therapies Be Used For Patients With Pts?mentioning
confidence: 99%